Perception of Global Self-Esteem and Body Fat in Adolescents Engaged in Basketball (Baltic Journal of Sport and Health Sciences, 2008)
Mental and moral maturity, growth, appearance, physical skills are nowadays more and more often used as reference points of our identity and emphasized in adolescence (Harter, 1999). Development of physical self-concept’s domains (e. g. appearance, self-esteem, physical competences, etc) has been a major concern among physical activity researchers during the last decade (Fox, 2000). The study examined the relation between the separate specific domains of physical self-concept: global self-esteem (the overall positive or negative feeling about one’s self) and body fat considering age and gender in adolescents — basketball players. Global self-esteem is understood as the overall positive or negative feeling about one’s self; or generalized feelings of self-worth which are not specific to a particular situation, but which apply to many activities or areas of life and predispose the subject to view new activities in particular ways (Macek, Lacinová, 2006). And body fat — an attitude towards you body fat directly (I think my stomach is too big; I have too much fat on my body; I am overweight; etc. (Marsh et al., 1994). Our study sample consisted of 95 adolescents — basketball players (54 males and 41 females) from different sport gymnasiums and clubs in Prague and Brno (Czech Republic). The respondents were divided into two age groups (Ist — 13—15 years of age and the IInd —16—18 years of age). An ordinary Introductory Questionnaire of 20 items was compiled in order to describe the population. The questionnaire was compiled by the first author of the current study. The variables were assessed by the Physical Self Description Questionnaire (PSDQ, Marsh et al., 1994). Both questionnaires were anonymous. To ensure uniformity in the administration of the questionnaire, the same set of directions were followed each time by the same researcher. To analyze the interaction effects for our researched factors (gender and age involvement), MANOVA (Multivariate Analysis of Variance) and correlation were calculated. Significance level was chosen to be 10%. The results proved our assumption that females tended to have more negative evaluation of the body fat then males regardless of their age. The second part focused on the measures of global self-esteem. The differences in the evaluation on global self-esteem were revealed by age, but not by gender. Global self-esteem was found to be more positive in younger adolescents —basketball players — than in older players regardless of their gender (p < 0.01).Keywords: global self-esteem, body fat, adolescence, age, gender, basketball.